2007
DOI: 10.4142/jvs.2007.8.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of h-telomerase reverse transcriptase in canine and feline meningiomas

Abstract: Telomere length maintenance is regarded as a fundamental step in tumorigenesis, as most human brain tumors, including meningiomas, stabilize the ends of their chromosomes using telomerase. This investigation represents an introduction to telomerase expression in canine and feline meningiomas. Twenty-five archived cases (14 dogs and 11 cats) were immunohistochemically tested for human-telomerase reverse transcriptase (h-TERT), scored, and quantified; furthermore, mitoses were counted on sections stained with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
2
24
0
1
Order By: Relevance
“…Maintenance of telomere length by telomerase is a carcinogenetic mechanism for many neoplasms. 8,16,23,28,37 Mast cell precursors undergo transient growth factor-mediated induction of telomerase activity during differentiation. 6 Human MCT cell lines tend to maintain a persistently high telomerase activity, uninfluenced by protein kinase or cell cycle inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of telomere length by telomerase is a carcinogenetic mechanism for many neoplasms. 8,16,23,28,37 Mast cell precursors undergo transient growth factor-mediated induction of telomerase activity during differentiation. 6 Human MCT cell lines tend to maintain a persistently high telomerase activity, uninfluenced by protein kinase or cell cycle inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…23,28 Human mast cell precursors have transient induction of telomerase activity, 6 but telomerase expression in feline MCTs has not been assessed.…”
mentioning
confidence: 99%
“…The cellular immortality‐related gene telomerase reverse transcriptase has been shown to be expressed in a variety of canine and feline brain tumors, and similar to human tumors has been associated with tumor grade 119, 120, 121. Similarly, overexpression of MMP‐2 and ‐9, E‐cadherin, claudin‐1, IL‐6, and cyclooxygenase‐2 has been documented in canine and feline meningiomas,121, 122, 123, 124, 125, 126 and MMP‐2/9 has been identified in canine gliomas and choroid plexus tumors 125.…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…25 Canine normal testis was used as a positive control for h-TERT. 26 An isotype-matched IgG negative control was run on each section.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a high proliferative index in the tumor is associated with low progesterone receptor (PR) concentration, suggesting that PR expression in canine and feline meningiomas is a reliable prognostic factor in the evaluation of this tumor, as well as in humans. 2,12,25,46 More recently, canine and feline meningiomas have been tested for telomerase immunoreactivity 22,26 and have produced contradictory results as to the correlation with the proliferative index.…”
Section: Introductionmentioning
confidence: 99%